Survival of Generic Escherichia coli on In-Field Mature and Immature Gala and Golden Delicious Apples With or Without Overhead Evaporative Cooling Treatment - Claire M Murphy; Kyu Ho Jeong; Lauren Walter; Manoella Mendoza; Tonia Green; Andy Liao; Karen Killinger; Ines Hanrahan; Mei-Jun Zhu (Journal of Food Protection)
The application of overhead evaporative cooling (EC) with untreated surface water is common in Washington State to decrease sunburn on apples. While this practice reduces crop and economic losses, applying untreated surface water to produce introduces potential risks of foodborne pathogen contamination. This study examined EC and the survival of inoculated generic Escherichia coli for two apple varieties over three growing seasons. Factors examined included EC treatment (conventional, untreated), canopy location (high, low), and apple variety (Gala, Golden Delicious). Fruit maturity (mature, immature) was also examined for one year. A rifampicin-resistant generic E. coli cocktail was applied to apples at 7.3 ± 0.4 log CFU/apple, and apples were enumerated for E. coli levels at 0, 2, 10, 18, 34, 42, 58, 82, 106, and 154 h postinoculation. Log-linear, Weibull, and Biphasic models were utilized to characterize the die-off pattern of E. coli. For most treatments, inoculated E. coli decreased by almost or over 6 log CFU/apple over the study duration; however, E. coli remained detectable at low levels on apples at 154 h postinoculation. EC treatment and canopy location did not significantly impact daily linear E. coli die-off rates. Apple variety and maturity demonstrated small but statistically significant impacts on daily linear die-off rates. Nonlinear models (i.e., biphasic and Weibull) best captured E. coli die-off on apples, showing a rapid initial decrease followed by a slower decline over time. Overall, results demonstrate that EC, a useful fruit quality practice, did not impact the survival of inoculated generic E. coli on apple surfaces. The study provides valuable insights for the apple industry regarding E. coli die-off rates on in-field apples, guiding practical decisions to mitigate risk.